A HPLC-ICP-AES technique for the screening of [XW11NbO40]n− aqueous solutions. (21st March 2018) - Shmakova, Alexandra A.; Akhmetova, Maria M.; Volchek, Victoria V.; Romanova, Tamara E.; Korolkov, Ilya; Sheven, Dmitri G.; Adonin, Sergey A.; Abramov, Pavel A.; Sokolov, Maxim N.
Abstract : In this research combined HPLC-ICP-AES technique was used to study formation of mixed [XW11 O40 ] n − (X = P, Ge, B) complexes. Abstract : The reaction of H3 [PW12 O40 ] with (NH4 )[NbO(C2 O4 )2 (H2 O)2 ]·3H2 O leads to the straightforward incorporation of Nb into a Keggin anion backbone resulting in [PW11 NbO40 ] 4− in nearly quantitative yield. Solution behavior of this monosubstituted anion as a function of pH was studied through 31 P NMR and HPLC-ICP-AES techniques (a combination of chromatography and ICP-AES). Increasing of the pH leads to the elimination of Nb from the structure with the formation of mixed Nb/W Lindqvist-type anions and monolacunary [PW11 O39 ] 7− . In aged solutions of [PW11 NbO40 ] 4− the formation of a mixture of [PNb2 W10 O39 ] 5− isomers was detected. The HPLC-ICP-AES technique was applied for the study of [BW11 O39 ] 9− behavior in aqueous solutions at different pH values and for monitoring the [GeW11 O39 ] 4− reaction with the niobium oxalate complex. Despite the presence of the nucleophilic NbO group [PW11 NbO40 ] 4− does not coordinate Co 2+ in DMF or Ni 2+ in CH3 CN, producing double [Co(DMF)6 ][PW11 NbO40 ]·2.6DMF (2 ) and [Ni(CH3 CN)5.5 (H2 O)0.5 ]2 [PW11 NbO40 ]·1.7CH3 CN (3 ) salts instead.